Developmental origins of osteoporotic fracture. - Cooper, C; Westlake, S; Harvey, N; Dennison, E (2009)
Osteoporosis is a skeletal disorder characterised by low bone mass and micro-architectural deterioration of bone tissue with a consequent increase in bone fragility and susceptibility to fracture.1 It is a widespread condition, often unrecognised in clinical practice, which may have devastating health consequences through its association with fragility fractures. The term 'osteoporosis' was first used in the nineteenth century as a histologic description for aged bone tissue, but its clinical consequences were not appreciated until Sir Astley Cooper recognised that hip fractures might result from an age-related reduction in bone mass or quality over 150 years ago. Since one disadvantage of a fracture-based definition is that diagnosis and treatment will be delayed when prevention is considered optimal treatment, an expert panel convened by the World Health Organisation (WHO) has suggested that both low bone mineral density (BMD) and fracture be combined in a stratified definition of osteoporosis.2 © 2009 Springer Netherlands.